The pluralism of norms regarding the family sphere: constraint or opportunity for the state of Senegal? - (:unkn) unknown (My University, 2013)
Panel The co‐regulation of society by the state: pluralism of norms and actors in the law reforms regarding the private sphere mod. Marieme Ndiaye et Céline Thiriot http://www.nomadit.co.uk/ecas/ecas2013/panels.php5?PanelID=1993
Keywords: African Research